Kemampuan Kerja antara Pekerja Lulusan SMA dan SMK di Industri Manufaktur: Studi Komparasi - Syamsul Hidayat; Muhammad Saleh (Valid: Jurnal Ilmiah, 2020)
This paper attempts to discuss the comparative work ability between high school and vocational school graduates in the manufacturing industry. The labor market in Indonesia in general is still dominated by high school and vocational school graduates. Work Abilities used in this study are Technical Ability, Conceptual Ability and Social Ability. The selected research method is a quantitative approach by distributing questionnaires to workers in companies in the Banten region, after the data collected are processed using the SPSS program. The analysis test uses normality test and different test uses Independent Samples Test. The results of the study showed that work ability had a significant difference between the workforce of high school and vocational high school graduates. Next discussion is discussed in this article